On estimation of high quantiles for certain classes of distributions - Stanojević, J. (Yugoslav Journal of Operations Research; Vol 25 No 2 (2015): Vol. 25 No. 2, 2016)
We investigate the rate of convergence of the direct-simulation estimator xp(n) of a large quantile xp of the Pareto and Gamma distributions. The upper bound of the probability P{|xp(n) - xp| ≥ ε} is determined.